Forum prepares leaders to tackle challenges of 21st century - Ruiz, Carolina (2009)
Presents brief reports on the participation of leaders from Jamaica, Antigua and Barbuda, Bahamas, Dominica, Belize and Barbados in fora organized by IICA's Centre for Leadership in Agriculture. The objective of the Forum is to prepare leaders with a global and modern vision of agriculture and rural life.